Determinants of Antimicrobial Resistance among the Different European Countries: More than Human and Animal Antimicrobial Consumption - Ana C. Silva; Paulo Jorge Nogueira; José-Artur Paiva (Antibiotics, 2021)
Although antimicrobial consumption is considered the main driver of antimicrobial resistance (AMR), other factors probably have a significant but less studied impact. The study’s goal was to assess AMR drivers across different European countries and quantify their possible contributions using the latest data available. Using the ESAC-Net (European Surveillance of Antimicrobial Consumption Network) database, the ESVAC (European Surveillance of Veterinary Antimicrobial Consumption) database and the OECD (Organisation for Economic Cooperation and Development) information, a dataset including 23 European countries was created. Associations between AMR and potential contributing factors were assessed using bivariate correlation and multiple linear regression models for multivariable analyses. Factors associated with the AMR rate among European countries were human ambulatory consumption of antibiotics and per capita expenditure on health, meaning that the higher human ambulatory consumption of antibiotics and the lower the per capita expenditure on health, the higher the AMR. Both variables together explain 74% of AMR variation. Private expenditure on health in terms of % GDP (Gross Domestic Profit) was positively related to a higher AMR rate. In conclusion, considering antibiotic consumption as the most important factor contributing to AMR may be a deviant focus, as resistance transmission may be paramount for AMR levels. Low per capita expenditure on health, probably a surrogate of worse healthcare conditions and a high level of resistance transmission, has a strong correlation with the AMR rate. Increasing public expenditure on healthcare, to strengthen infection control structures and processes interventions, seems relevant to tackle antimicrobial resistance at the European scale.